Evaluation of Advertising Images with Laptop Camera Eye Tracking - Pavlov, N.V.; Pantyuhina, P.O.; Zotova, E.A.; Shaban, A.P. (BUKETOV BUSINESS REVIEW, 2023)
Object: The goal of this article is to evaluate the quality of the eye tracking method for studying the perception of advertising images using a laptop camera. Methods: The method of scientific experiment was chosen as the main method of research, with hypotheses, their verification, confirmation or refutation. For processing the results, the calculation of the mean value of the percentage of fixation and t-test were used to determine the statistical significance of differences in the results. Findings: Options were developed to improve the eye tracking method: recommendations to improve the reliability of the results, and factors influencing the respondent’s actions were identified. The described methods for improving the quality of images are of a qualitative nature. The main criteria for obtaining the most reliable result when working with a focus group are determined. The necessity of using artificial intelligence to combine eye-catching areas of drawings with a heat map is revealed. Recommendations for teaching the use of the research method under consideration are given. Conclusions: An eye tracking tool using a laptop camera was evaluated. Possible reasons for the distortion of the results were identified. The ways of further improvement of the tool, methods of its use and processing of the obtained results were proposed. Due to the limited sample size, the reasoning is qualitative. Possible directions for further work are identified.